Therapeutic concentrations of antidepressants inhibit pancreatic beta-cell function via mitochondrial complex inhibition - Elmorsy, Ekramy; Al-Ghafari, Ayat; Helaly, Ahmed; Hisab, Ahmed S.; Oehrle, Bettina; Smith, Paul A. (Oxford University Press, 2017)
Diabetes mellitus risk is increased by prolonged usage of antidepressants (ADs). Although various mechanisms are suggested for their diabetogenic potential, whether a direct effect of ADs on pancreatic β-cells is involved is unclear. We examined this idea for 3 ADs: paroxetine, clomipramine and, with particular emphasis, fluoxetine, on insulin secretion, mitochondrial function, cellular bioenergetics, KATP channel activity, and caspase activity in murine and human cell-line models of pancreatic β-cells. Metabolic assays showed that these ADs decreased the redox, oxidative respiration, and energetic potential of β-cells in a time and concentration dependent manner, even at a concentration of 100 nM, well within the therapeutic window. These effects were related to inhibition of mitochondrial complex I and III. Consistent with impaired mitochondrial function, lactate output was increased and insulin secretion decreased. Neither fluoxetine, antimycin nor rotenone could reactivate KATP channel activity blocked by glucose unlike the mitochondrial uncoupler, FCCP. Chronic, but not acute, AD increased oxidative stress and activated caspases, 3, 8, and 9. A close agreement was found for the rates of oxidative respiration, lactate output and modulation of KATP channel activity in MIN6 cells with those of primary murine cells; data that supports MIN6 as a valid model to study beta-cell bioenergetics. To conclude, paroxetine, clomipramine and fluoxetine were all cytotoxic at therapeutic concentrations on pancreatic beta-cells; an action suggested to arise by inhibition of mitochondrial bioenergetics, oxidative stress and induction of apoptosis. These actions help explain the diabetogenic potential of these ADs in humans.